2011
DOI: 10.1016/j.stem.2011.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming of Mouse and Human Cells to Pluripotency Using Mature MicroRNAs

Abstract: Induced pluripotent stem cells (iPSCs) can be generated from differentiated human and mouse somatic cells using transcription factors such as Oct4, Sox2, Klf4, and c-Myc. It is possible to augment the reprogramming process with chemical compounds, but issues related to low reprogramming efficiencies and, with a number of protocols, residual vector sequences, remain to be resolved. We show here that it is possible to reprogram mouse and human cells to pluripotency by direct transfection of mature double-strande… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
520
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 688 publications
(531 citation statements)
references
References 30 publications
5
520
1
1
Order By: Relevance
“…1a). In brief, RNA-iPSCs are reprogrammed from human skin fibroblasts by a single transfection of an miR cocktail (miR-200c, miR-302a-d and miR-369) 31 and subsequent daily transfections of mature mRNA transcripts encoding Klf4, Oct4, Sox2, c-Myc and Lin28 for 10-12 d, until the formation of mature iPSC colonies 32 (Fig. 1b).…”
Section: Resultsmentioning
confidence: 99%
“…1a). In brief, RNA-iPSCs are reprogrammed from human skin fibroblasts by a single transfection of an miR cocktail (miR-200c, miR-302a-d and miR-369) 31 and subsequent daily transfections of mature mRNA transcripts encoding Klf4, Oct4, Sox2, c-Myc and Lin28 for 10-12 d, until the formation of mature iPSC colonies 32 (Fig. 1b).…”
Section: Resultsmentioning
confidence: 99%
“…In 2008, Lin and colleagues reported the transformation of human skin cancer cells into an ES-like state by overexpression of the miR302 cluster . Very recently, two independent groups announced highly efficient generation of mouse and human iPSCs either by lentiviral delivery of miR302 into fibroblast cells or by transfection of mature miR200c, miR302, and mir369 (Anokye-Danso et al, 2011;Miyoshi et al, 2011). These microRNA iPSCs were indistinguishable from OSKM-iPSCs in pluripotency marker expression, teratoma formation, and germline transmission (in mice).…”
Section: Generating Ips Cells By Micrornasmentioning
confidence: 99%
“…56 Two independent groups have now demonstrated that lentiviral expression of miR-302/ miR-367 cluster and a cocktail of miRNAs (miR-200c, miR302a-d, miR-369-3p, and miR-369-5p) may reprogram human fibroblasts to iPSCs efficiently. 57 The cells that reexpressed human ESC factors featuring global gene expression analogous to human ESCs were named miRNA-iPSCs. This constitutes the first proof of principle to demonstrate that iPSCs may be obtained with miRNAs without the need for genomic integration of foreign DNA.…”
Section: Mirnas In Cellular Reprogrammingmentioning
confidence: 99%